(untitled) - Jacobs, Danny O. (New York, 2007)
First exposure to general surgery is the book they wish they'd had for their GS clerking. The ideal databank and toolset for your rotation FIRST EXPOSURE: To GENERAL SURGERY enhances your rotation with: A compelling profile of the practice of general surgery Just the right amount of material for your 4-week clerkship Detailed descriptions of procedures you will see and perform A focus on important concepts you should learn-not memorization of facts How-to's for evaluating the surgical patient Clinically relevant detail on cases you will see FIRST EXPOSURE SERIES BOOKS PHYSICIANS WISH THEY HAD IN THEIR CLERKSHIPS Just the right amount of information to read and absorb during your clerkship An orientation to each specialty and the ways it differs from other specialties What you can expect to get from your clerkship Clinically helpful information on the procedures you will see and perform A breakdown of the "Chief Complaints" you are most likely to encounter, with a table of "Don't-Miss Diagnoses" Essential information on common diseases and conditions seen in each specialty Adding value to the clerkship experience-that's what First Exposure is all about.
Keywords: Surgery,Giải phẩu; Problems, exercises, etc.,Vấn đề, bài tập,v.v..